Portrayal of motherhood by female authors in American literature in the Light of The Awakening, Herland and The Narrow House - Tanjim, Taslima (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.